Revisiting CIPAA 2012 implementation: Addressing conditional payment and promoting sustainable payment flow in Malaysian Construction - Muhamad Basir, Puteri Nur Farah Ezzati; Zainuddin, Mohd Firdaus; Shuib, Mohammad Nasharudine; Mamat, Mohd Esham; Zainal Abidin, Zaiwannizar; Abdullah, Mohd Nazri (Journal of Islamic, Social, Economics and Development, 2025)
The Malaysian construction industry continues to face persistent payment issues, particularly affecting subcontractors. One major contributor is the enforcement of "pay-when paid" clauses, which delay payments and disrupt project cash flows. In response, the Construction Industry Payment and Adjudication Act (CIPAA) 2012 was introduced to eliminate unfair payment practices and provide a fast, cost-effective dispute resolution mechanism. Yet, payment issues have not been eliminated even though this Act has been implemented for more than 10 years. This study investigates the implementation and impact of CIPAA 2012, with a focus on awareness and experiences among G1–G3 contractors in Perak Tengah. A quantitative methodology was employed using structured questionnaires, yielding 106 valid responses. Findings reveal that "pay-when-paid" clauses remain the leading cause of payment disputes. Despite nearly 90% of respondents having subcontracting experience, only 65% were aware of CIPAA, and less than half understood their rights under the Act. The study highlights the need for increased awareness, better enforcement, and structural reforms to ensure sustainable payment practices within the Malaysian construction industry.